Acquisition of turn-taking in sign language conversations: An overview of language modality and turn structure - Horton, Laura; Singleton, Jenny (Frontiers in Psychology, 2022)
The task of transitioning from one interlocutor to another in conversation – taking turns – is a complex social process, but typically transpires rapidly and without incident in conversations between adults. Cross-linguistic similarities in turn timing and turn structure have led researchers to suggest that it is a core antecedent to human language and a primary driver of an innate “interaction engine.” This review focuses on studies that have tested the extent of turn timing and turn structure patterns in two areas: across language modalities and in early language development. Taken together, these two lines of research offer predictions about the development of turn-taking for children who are deaf or hard of hearing (DHH) acquiring sign languages. We introduce considerations unique to signed language development – namely the heterogenous ecologies in which signed language acquisition occurs – suggesting that more work is needed to account for the diverse circumstances of language acquisition for DHH children. We discuss differences between early sign language acquisition at home compared to later sign language acquisition at school in classroom settings, particularly in countries with national sign languages. We also compare acquisition in these settings to communities without a national sign language where DHH children acquire local sign languages. In particular, we encourage more documentation of naturalistic conversations between DHH children who sign and their caregivers, teachers, and peers. Further, we suggest that future studies should consider: visual/manual cues to turn-taking and whether they are the same or different for child or adult learners; the protracted time-course of turn-taking development in childhood, in spite of the presence of turn-taking abilities early in development; and the unique demands of language development in multi-party conversations that happen in settings like classrooms for older children versus language development at home in dyadic interactions.